Osseointegration improvement of Co-Cr-Mo alloy produced by additive manufacturing - Iatecola, Amilton (2022)
Cobalt-base alloys (Co-Cr-Mo) are widely employed in dentistry and orthopedic implants due to their biocompatibility, high mechanical strength and wear resistance. The osseointegration of implants can be improved by surface modification techniques. However, complex geometries obtained by additive manufacturing (AM) limits the efficiency of mechanical-based surface modification techniques. Therefore, plasma immersion ion implantation (PIII) is the best alternative, creating nanotopography even in complex structures. In the present study, we report the osseointegration results in three conditions of the additively manufactured Co-Cr-Mo alloy: (i) as-built, (ii) after PIII, and (iii) coated with titanium (Ti) followed by PIII. The metallic samples were designed with a solid half and a porous half to observe the bone ingrowth in different surfaces. Our results revealed that all conditions presented cortical bone formation. The titanium-coated sample exhibited the best biomechanical results, which was attributed to the higher bone ingrowth percentage with almost all medullary canals filled with neoformed bone and the pores of the implant filled and surrounded by bone ingrowth. It was concluded that the metal alloys produced for AM are biocompatible and stimulate bone neoformation, especially when the Co-28Cr-6Mo alloy with a Ti-coated surface, nanostructured and anodized by PIII is used, whose technology has been shown to increase the osseointegration capacity of this implant.